Epithelioid Hemangioendothelioma of the Mastoid: Resection for Recurrence and Adjuvant Radiation with 8-Year Followup - Doniel Drazin; Ravi Gandhi; Elzbieta Slodkowska; Alan S. Boulos (Case Reports in Surgery)
Epithelioid hemangioendothelioma (EH) is a rare, vascular neoplasm that can affect any age group and has been reported previously in sites including bone, liver, lung, breast, and brain. We describe a case of EH located in the mastoid, which appears to be the first report of EH in this site. The patient was 62 years old when they presented with dizziness and nausea. A suboccipital surgical approach was utilized to resect the tumor. After 18-month followup, the patient was symptom-free; however, imaging demonstrated a recurrence and the patient was taken back to the operating room for a resection. There is no evidence of recurrence after 8 years of followup. This paper aims to reinforce the need for a timely radical excision and aggressive clinical followup as the best hope for cure. Here, we describe an illustrative case and review the pertinent literature.